Skip to main content\(\require{cancel}\newcommand{\highlight}[1]{{\color{blue}{#1}}}
\newcommand{\ds}{\displaystyle}
\newcommand{\fp}{f'}
\newcommand{\fpp}{f''}
\newcommand{\lz}[2]{\frac{d#1}{d#2}}
\newcommand{\lzn}[3]{\frac{d^{#1}#2}{d#3^{#1}}}
\newcommand{\lzo}[1]{\frac{d}{d#1}}
\newcommand{\lzoo}[2]{{\frac{d}{d#1}}{\left(#2\right)}}
\newcommand{\lzon}[2]{\frac{d^{#1}}{d#2^{#1}}}
\newcommand{\lzoa}[3]{\left.{\frac{d#1}{d#2}}\right|_{#3}}
\newcommand{\plz}[2]{\frac{\partial#1}{\partial#2}}
\newcommand{\plzoa}[3]{\left.{\frac{\partial#1}{\partial#2}}\right|_{#3}}
\newcommand{\inflim}[1][n]{\lim\limits_{#1 \to \infty}}
\newcommand{\infser}[1][1]{\sum_{n=#1}^\infty}
\newcommand{\Fp}{F\primeskip'}
\newcommand{\Fpp}{F\primeskip''}
\newcommand{\yp}{y\primeskip'}
\newcommand{\gp}{g\primeskip'}
\newcommand{\dx}{\Delta x}
\newcommand{\dy}{\Delta y}
\newcommand{\ddz}{\Delta z}
\newcommand{\thet}{\theta}
\newcommand{\norm}[1]{\left\lVert#1\right\rVert}
\newcommand{\vnorm}[1]{\left\lVert\vec #1\right\rVert}
\newcommand{\snorm}[1]{\left|\left|\,#1\,\right|\right|}
\newcommand{\la}{\left\langle}
\newcommand{\ra}{\right\rangle}
\newcommand{\dotp}[2]{\vec #1 \cdot \vec #2}
\newcommand{\proj}[2]{\text{proj}_{\,\vec #2}{\,\vec #1}}
\newcommand{\crossp}[2]{\vec #1 \times \vec #2}
\newcommand{\veci}{\vec i}
\newcommand{\vecj}{\vec j}
\newcommand{\veck}{\vec k}
\newcommand{\vecu}{\vec u}
\newcommand{\vecv}{\vec v}
\newcommand{\vecw}{\vec w}
\newcommand{\vecx}{\vec x}
\newcommand{\vecy}{\vec y}
\newcommand{\vrp}{\vec r\hskip0.75pt '}
\newcommand{\vrpp}{\vec r\hskip0.75pt ''}
\newcommand{\vsp}{\vec s\hskip0.75pt '}
\newcommand{\vrt}{\vec r(t)}
\newcommand{\vst}{\vec s(t)}
\newcommand{\vvt}{\vec v(t)}
\newcommand{\vat}{\vec a(t)}
\newcommand{\px}{\partial x}
\newcommand{\py}{\partial y}
\newcommand{\pz}{\partial z}
\newcommand{\pf}{\partial f}
\newcommand{\unittangent}{\vec{{}T}}
\newcommand{\unitnormal}{\vec{N}}
\newcommand{\unittangentprime}{\vec{{}T}\hskip0.75pt '}
\newcommand{\R}{mathbb{R}}
\newcommand{\mathN}{\mathbb{N}}
\newcommand{\surfaceS}{\mathcal{S}}
\newcommand{\zerooverzero}{\ds \raisebox{8pt}{\text{``\ }}\frac{0}{0}\raisebox{8pt}{\textit{ ''}}}
\newcommand{\deriv}[2]{\myds\frac{d}{dx}\left(#1\right)=#2}
\newcommand{\myint}[2]{\myds\int #1\, dx= {\ds #2}}
\newcommand{\primeskip}{\hskip.75pt}
\newcommand{\abs}[1]{\left\lvert #1\right\rvert}
\newcommand{\sech}{\operatorname{sech}}
\newcommand{\csch}{\operatorname{csch}}
\newcommand{\curl}{\operatorname{curl}}
\newcommand{\divv}{\operatorname{div}}
\newcommand{\Hess}{\operatorname{Hess}}
\newcommand{\lt}{<}
\newcommand{\gt}{>}
\newcommand{\amp}{&}
\definecolor{fillinmathshade}{gray}{0.9}
\newcommand{\fillinmath}[1]{\mathchoice{\colorbox{fillinmathshade}{$\displaystyle \phantom{\,#1\,}$}}{\colorbox{fillinmathshade}{$\textstyle \phantom{\,#1\,}$}}{\colorbox{fillinmathshade}{$\scriptstyle \phantom{\,#1\,}$}}{\colorbox{fillinmathshade}{$\scriptscriptstyle\phantom{\,#1\,}$}}}
\)
Section B.2 Integration Formulas
List B.2.1. Basic Rules
\(\displaystyle \int c\cdot f(x)\,dx=c\int f(x)\,dx\)
\(\displaystyle \int \bigl(f(x)\pm g(x)\bigr)\,dx = \int f(x)\, dx \pm \int g(x)\, dx\)
\(\displaystyle \int 0\,dx = C\)
\(\displaystyle \int 1\,dx=x+C\)
List B.2.2. Integrals of Elementary (non-Trig) Functions
\(\displaystyle \int e^x\,dx=e^x+C\)
\(\displaystyle \int \ln x\,dx=x\ln x -x +C\)
\(\displaystyle \int a^x\,dx=\frac{1}{\ln a}\cdot a^x+C\)
\(\displaystyle \int \frac{1}{x}\,dx =\ln \abs{x} + C\)
\(\displaystyle \int x^n\,dx=\frac{1}{n+1}x^{n+1}+C, n\neq -1\)
List B.2.3. Integrals Involving Trigonometric Functions
\(\displaystyle \int \cos x\,dx=\sin x+C\)
\(\displaystyle \int \sin x\,dx=-\cos x+C\)
\(\displaystyle \int \tan x\,dx=-\ln \abs{\cos x}+C\)
\(\displaystyle \int \sec x\,dx=\ln \abs{\sec x+\tan x}+C\)
\(\displaystyle \int \csc x\,dx=-\ln \abs{\csc x+\cot x}+C\)
\(\displaystyle \int \cot x\,dx=\ln \abs{\sin x}+C\)
\(\displaystyle \int \sec^2 x\,dx=\tan x+C\)
\(\displaystyle \int \csc^2x\,dx=-\cot x+C\)
\(\displaystyle \int \sec x\tan x\,dx=\sec x+C\)
\(\displaystyle \int \csc x\cot x\,dx=-\csc x+C\)
\(\displaystyle \int \cos^2x\,dx=\frac12x+\frac14\sin\big(2x\big)+C\)
\(\displaystyle \int \sin^2x\,dx=\frac12x-\frac14\sin\big(2x\big)+C\)
\(\displaystyle \int \frac{1}{x^2+a^2}\,dx = \frac1a\tan^{-1}\left(\frac xa\right)+C\)
\(\displaystyle \int \frac{1}{\sqrt{a^2-x^2}} = \sin^{-1}\left(\frac xa\right)+C\)
\(\displaystyle \int \frac{1}{x\sqrt{x^2-a^2}} = \frac1a\sec^{-1}\left(\frac{\abs{x}}{a}\right)+C\)
List B.2.4. Integrals Involving Hyperbolic Functions
\(\displaystyle \int \cosh x\,dx=\sinh x+C\)
\(\displaystyle \int \sinh x\,dx=\cosh x+C\)
\(\displaystyle \int \tanh x\,dx=\ln(\cosh x)+C\)
\(\displaystyle \int \coth x\,dx=\ln \abs{\sinh x}+C\)
\(\displaystyle \int \frac{1}{\sqrt{x^2-a^2}}\, dx =\ln\abs{x+\sqrt{x^2-a^2}}+C\)
\(\displaystyle \int \frac{1}{\sqrt{x^2+a^2}}\, dx=\ln\abs{x+\sqrt{x^2+a^2}}+C\)
\(\displaystyle \int \frac{1}{a^2-x^2}\, dx =\frac{1}{2a}\ln\abs{\frac{a+x}{a-x}}+C\)
\(\displaystyle \int \frac{1}{x\sqrt{a^2-x^2}}\, dx = \frac{1}{a}\ln\left(\frac{x}{a+\sqrt{a^2-x^2}}\right)+C\)
\(\displaystyle \int \frac{1}{x\sqrt{x^2+a^2}}\, = \frac{1}{a}\ln\abs{\frac{x}{a+\sqrt{x^2+a^2}}}+C\)